The Effect of Entonox on the Apgar Scores of Infants Born to Mothers Requesting Painless Deliveries at Motahari Hospital in Jahrom City: A Double-Blind Clinical Trial - Hasan Zabetian (Journal of Global Pharma Technology, 2017)
Introduction A vaginal delivery is one of the hard pains during a woman’s life. Therefore, different training methods or interventions have been employed in developed countries to encourage women to use Entonox for painless and safe deliveries. This study was conducted to investigate the effect of Entonox on the Apgar scores of infants born to mothers requesting painless deliveries at Motahari Hospital in Jahrom City. Method: In this double-blind clinical trial, the random sampling method was in Motahari Hospital in Jahrom City. The research sample included all of the parturient women requesting a vaginal delivery under the supervision of a gynecologist. The subjects were divided randomly into the experimental group (39 individuals receiving Entonox) and the control group (41 individuals). The descriptive statistics and the nonparametric Mann-Whitney test were used to analyze data in SPSS 18.Results The average ages of the experimental group (receiving Entonox) and the control group (non-receiving Entonox) were 25-26 years. The majority of parturient women had one child. In experimental group, the most prevalent complications of Entonox were xerostomia (13; 39.4%) and somnolence (10; 30.3%). The results of the Mann-Whitney test indicated that there was not a statistically significant difference between the two groups in terms of the Apgar scores of the newborn babies (p-value>0.05). Moreover, the vital signs of patients (systolic and diastolic blood pressures, heartbeat, and SpO2) did not show any significant differences in the experimental group receiving Entonox over time (1-5) (p-value>0.05).Conclusion use of Entonox was a safe method ,fewer complications for parturient women and her infant during delivery in comparison with other methods. Moreover, the analgesic efficacy of this gas is considerable.Keywords: Entonox, Parturient women, Apgar scores, Infants, Anesthesia.